THE EFFECTIVENESS OF PROJECT BASED LEARNING MODEL TO IMPROVE STUDENTS VOCATIONAL SKILLS - Wicaksana, Ervan Johan; Maridi, Maridi; Sutarno, Sutarno (Unnes Science Education Journal, 2017)
The purpose of this study was to determine the extent of the effectiveness of the Model Project Based Learning (PjBL)to improving students vocational skills. The sample of this research is 60 vocational students were divided into two classes, namely the control class and the experimental class. Data were analyzed using independent sample t-test. The result of this research showed that the PjBL is effective to improve the students' vocational skills. It is proved from the t-test results there is t count > t table (6.929 > 2.002) and p <0.05 (0.00 <0.05).